The concept of territorial cohesion - how to apply it to monitoring development of northern Polish regions - Jacek SołTys (European Regional Science Association (ERSA), 2011)
Territorial cohesion (TC) is a multi dimensional concept, but lacking precision and not easy to be operationalized. Analysed are different scopes (or segments) of the concept and the indicators of its implementation in policy planning and decisionmaking. Amongst the already used in practice or being proposed by other authors. In the focus more interest is devoted to those which concern the segments seldomly touched so far like place- based development potential of a given territory or its landscape identity. The author recognises all the indicators of TC in the context of regional sustainable development monitoring system. The availablity of information and relevancy for solving development issues are criteria proposed to use for assessment and selection of the relevant indicators for regions in northern Poland. Their feasibility are checked at the NUTS2 and NUTS3 levels.
Keywords: 330